final-exam-solutions

final-exam-solutions - MthSc 810 – Mathematical...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MthSc 810 – Mathematical Programming Solutions to the final exam, Fall 2011. Problem 1 (5 pts.): 1. Prove that the set S = { ( x 1 ,x 2 ) : x 1 x 2 ≥ 1 ,x 1 > ,x 2 > } is convex. A. : There are several ways. First, note that x 1 x 2 ≥ 1 ⇔ x 2 ≥ 1 x 1 ⇔ 1 x 1 − x 2 ≤ 0, a convex constraint given that 1 x 2 is convex for x 2 > 0. Another way is as follows: since we want to prove that ∀ x ′ ∈ S, x ′′ ∈ S,λ x ′ +(1 − λ ) x ′′ ∈ S , we need to prove x ′ 1 x ′ 2 ≥ 1 ∧ x ′′ 1 x ′′ 2 ≥ 1 ⇒ ( λx ′ 1 +(1 − λ ) x ′′ 1 )( λx ′ 2 +(1 − λ ) x ′′ 2 ) ≥ 1. To this purpose, let’s take the logarithm of both sides (which exists since S ⊂ R 2 + ): ( λx ′ 1 + (1 − λ ) x ′′ 1 )( λx ′ 2 + (1 − λ ) x ′′ 2 ) ≥ 1 ⇔ log( λx ′ 1 + (1 − λ ) x ′′ 1 ) + log( λx ′ 2 + (1 − λ ) x ′′ 2 ) ≥ . log( λx ′ 1 + (1 − λ ) x ′′ 1 ) + log( λx ′ 2 + (1 − λ ) x ′′ 2 ) ≥ λ log x ′ 1 + (1 − λ ) log x ′′ 1 + λ log x ′ 2 + (1 − λ ) log x ′′ 2 = λ log( x ′ 1 x ′ 2 ) + (1 − λ ) log( x ′′ 1 x ′′ 2 ) = 0 , the third inequality a consequence of the logarithm being a concave function. 2. Prove that the set G = { α ∈ R + : 1 ≥ min { αx : x ≥ 1 }} is convex. A. : Note that min { αx : x ≥ 1 } = α for any α ≥ 0, hence G = { α ∈ R + : α ≤ 1 } = [0 , 1], which is convex. Problem 2 (15 pts.): Consider the problem min − 3 x 1 + x 2 s.t. x 1 − x 2 − x 3 = 1 2 x 1 − x 2 + x 4 = 4 x 1 , x 2 , x 3 , x 4 ≥ . 1. The basis B = { 2 , 4 } is neither primal nor dual feasible. However, there is one pivoting operation that suffices to obtain a basis that is either primal or dual feasible. Carry out that pivoting operation and write the resulting dictionary (or tableau). A. : First dictionary: x 2 = − 1 + x 1 − x 3 x 4 = 3 − x 1 − x 3 z = − 1 − 2 x 1 − x 3 . Let’s try to obtain primal feasibility. To this purpose, x 3 can’t help because x 3 > 0 means x 2 < − 1, so let x 1 enter the basis. For x 1 = 1 we get back primal feasibility while x 2 becomes nonbasic, and this would be the corre- sponding dictionary: x 1 = 1 + x 2 + x 3 x 4 = 2 − x 2 − 2 x 3 z = − 3 − 2 x 2 − 3 x 3 . 2. Consider again the first basis, and suppose you could change a coefficient of x 1 or x 3 in any of the two linear constraints. Does any such change make the solution primal feasible? Explain. Note: there is no need to try any change....
View Full Document

This note was uploaded on 03/14/2012 for the course MTHSC 810 taught by Professor Staff during the Fall '08 term at Clemson.

Page1 / 5

final-exam-solutions - MthSc 810 – Mathematical...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online